Reducing Readmissions Using Teach-Back: Enhancing Patient and Family Education. (January 2015) - Peter, Debra; Robinson, Paula; Jordan, Marie; Lawrence, Susan; Casey, Krista; Salas-Lopez, Debbie
Abstract : This article describes a quality improvement initiative, implemented by a patient education workgroup within a tertiary Magnet® facility. The project focused on the association between inadequate care transitions in patients with heart failure and subsequent costly readmissions. The teach-back initiative was piloted with patients hospitalized with heart failure, because of this population's high risk of readmission. Learning outcomes included documented improvements in patients' understanding of their disease and reduced readmission rates. Abstract : Supplemental Digital Content is available in the text.